2003
DOI: 10.1590/s0074-02762003000200005
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of Aedes aegypti and Aedes albopictus (Diptera: Culicidae) in an urban endemic dengue area in the State of Rio de Janeiro, Brazil

Abstract: Experimental releases of female Aedes (Stegomyia) aegypti and Aedes (Stegomyia) albopictus were performed in August and September 1999, in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
233
1
13

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 304 publications
(257 citation statements)
references
References 21 publications
10
233
1
13
Order By: Relevance
“…CEP/ FIOCRUZ allowed mark, release and recapture experiments with Ae. aegypti females without cut proboscis as in Honório 29 , since this amputation might influence female host-seeking behavior and consequently dispersal patterns and survival rates. As a counterpart, we committed ourselves to suspend mosquito release if any dengue case was registered in the study area before or even during the experiment.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…CEP/ FIOCRUZ allowed mark, release and recapture experiments with Ae. aegypti females without cut proboscis as in Honório 29 , since this amputation might influence female host-seeking behavior and consequently dispersal patterns and survival rates. As a counterpart, we committed ourselves to suspend mosquito release if any dengue case was registered in the study area before or even during the experiment.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…aegypti remains controversial because recorded dispersal distances have been variable. Honorio et al (2003) observed dispersal at distances between 100-800 m in an urban area of the state of Rio de Janeiro (RJ), Brazil. However, Harrington et al (2005), in experiments conducted in Puerto Rico and Thailand, found that most individuals disperse a few tens of meters and very few individuals disperse up to 500 m.…”
mentioning
confidence: 99%
“…These authors released gravid mosquitoes previously blood-fed on a solution of RbCl in citrated pig blood. Honório et al (2003) also estimated flight ranges of mosquitoes in an endemic dengue area in Rio de Janeiro (Lourenço-de-Oliveira et al 2002) monitoring eggs of released Ae. aegypti and Ae.…”
mentioning
confidence: 99%
“…Accordingly, the concentration of 0.025 M RbCl diluted in an artificial blood meal was considered the ideal and thus used in the experiment described bellow. Coincidentally, this concentration was the same used in the field works by Reiter et al (1995) and Honório et al (2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation